Synthesis of CdS Nanoparticles Using The Brimstone - Suryajaya, Suryajaya; Safitri, Ayu; Suarso, Eka; Haryanti, Ninis Hadi; Manik, Tetti Novalina; Darminto, Darminto (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2024)
This paper explains and demonstrates how to synthesize Cadmium Sulphide (CdS) nanoparticles (NPs) using brimstone. The brimstone is obtained from Ijen volcanic crater in East Java Indonesia and used as the source of sulfur gas (S2) instead of Na2S. The brimstone was crushed and dissolved in potassium hydroxide (KOH) solution while heated. Acetic acid (CH3COOH) was added, to release the S2 gas. The liquid-gas method was used to prepare the CdS colloid solution. In this study, the effect of variations in the concentration and volume of CH3COOH, temperature variation, and exposure time on the synthesis of colloidal solutions of CdS NPs will be investigated. The absorption edge of the CdS colloidal solution compared to the bulk material experienced a blue shift. This is the evidence of the formation of NPs in solution. It is confirmed by FTIR which shows a CdS absorption peak at 467 cm-1. The radius of CdS NPs was calculated using the Efros equation to obtain a result of approximately 2 nm. Particle size analyzer (PSA) provides a much larger particle size of 20.8 nm. It is assumed that the NPs were agglomerated. Several treatments given, such as varying the volume of CH3COOH, varying temperature, stirring, and varying synthesis time, did not affect the size of the NPs. The cadmium sulfide produced would be used as photocatalist in water treatment application.